Gold and bubbles: an impossible binomial? A review of historical and current evidence. Issue 3 (6th February 2022) - Beretta, Edoardo; Peluso, Stefano
ABSTRACT: Gold has a far-reaching history of 'safe haven' or 'anchor of stability'. However, the epitome of precious metals has recently deviated from its historical price trend. Fluctuations and volatility have increased too. We argue that gold is not subject to bubbles (due to its scarcity in nature), although its price is. By means of a logical-analytical macroeconomic approach combined with statistical and empirical evidence, we prove that there is excess liquidity in the world economy as a whole, which has been increasingly invested in this precious metal. The paper also shows why the gold price could further rise and/or suddenly decrease. Both scenarios would be possible as soon as speculation kicks in.